2019
DOI: 10.32479/ijefi.7767
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trade Agreements and Foreign Direct Investment on Trade: Evidence From Vietnam

Abstract: In recent years, Vietnam has embarked on trade liberalisation leading to increased trade flows, as well as benefiting from increased foreign direct investment (FDI) inflows. This paper analyses the impacts of a range of trade agreements and FDI inflows on Vietnamese trade flows. We offer new insights through considering which of the key trade agreements have been more efficient in expanding Vietnamese trade, and how the sensitivity of trade to FDI has changed as a result. The estimation of gravity models over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…The effect of FDI on Indonesia's non-oil and gas exports in the global value model and developing countries are in line with previous studies ( Sun and Parikh, 2001 ; Rahmaddi and Ichihashi, 2013 ; Mijiyawa, 2015 ; Chiappini, 2016 ; Duong et al., 2019 ). FDI in both models has a significant effect on Indonesia's non-oil and gas exports, however, the FDI coefficient is relatively small compared to the coefficient on other independent variables.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The effect of FDI on Indonesia's non-oil and gas exports in the global value model and developing countries are in line with previous studies ( Sun and Parikh, 2001 ; Rahmaddi and Ichihashi, 2013 ; Mijiyawa, 2015 ; Chiappini, 2016 ; Duong et al., 2019 ). FDI in both models has a significant effect on Indonesia's non-oil and gas exports, however, the FDI coefficient is relatively small compared to the coefficient on other independent variables.…”
Section: Resultssupporting
confidence: 90%
“…Appleyard et al (2011) stated a similar thing that in the long run, the depreciation will cause an increase in exports. The estimation results of this study for the nominal exchange rate in both models support previous research which concluded that the exchange rate has a positive impact on export value (Sun and Parikh, 2001;Kang, 2011;Rahmaddi and Ichihashi, 2013;Mijiyawa, 2015;Duong et al, 2019).…”
Section: Resultssupporting
confidence: 87%
“…In the year 2001, Vietnam's MI showed a sharp increase of 39% and 34% on the production and consumption sides, respectively. The main reason for this massive expansion in material consumption was found to be the signing of the Bilateral Trade Agreement (BTA) between the United States and Vietnam in 2000, granting the Normal Trade Relations (NTR) status, opening up access to the US market and facilitating foreign investment, driving Vietnam's shift into an export-oriented economy [73]. This trade liberalization in Vietnam, coupled with a 10-year economic plan promoting the private sector [74], contributed to the annual GDP growth, averaging 7.1% from 2000 to 2004, reaching 8.4% in 2005, and attracting global attention for its rapid economic expansion [75].…”
Section: Materials Usementioning
confidence: 99%